Study of Relationship Between Some Climate Elements and Growth of Arabica Coffee Plants (Coffea arabica L.) Under Forest Plant Stands - Erdien, Ghifani Erdien; Hariyono, Didik (Department of Agronomy, Faculty of Agriculture, Brawijaya University, 2024)
Coffee (Coffea sp.) is one of the plants that play an important role in farming in Indonesia. The country with the third largest coffee producer in the world and a beneficiary of foreign exchange, the coffee commodity is important to improve its quality and quantity. The production of Arabica coffee is still not consistent in its results, efforts are being made to increase production yields by looking at the growth of Arabica coffee plants against environmental factors such as climate elements. This study aims to determine the relationship between the growth of arabica coffee (Coffea acabica L.) and environmental factors such as climate elements. The research was carried out from March to June 2020 in UB Forest's educational forest. Tools and materials used are caliper, alvaboard, markers, machetes, cameras, observation data, and data on climate elements in 2015-2016. The research method uses a survey method by not giving treatment (proportional observation). The sampling technique used purposive sampling method. The primary data collection technique is in the form of research data and secondary data in the form of climate element data. Observations were made to count the number of shoots (flush), the number of branches, and the number of fruit bunches, and to measure the diameter of the stem. Descriptive analysis, analyzing monthly climate data, determining the type of climate according to Schmidt-Ferguson, and analyzing the correlation test between Arabica coffee plant growth data and climate element data. The results showed that the number of shoots (flush) had a relationship with climate, air temperature and rainfall, stem diameter did not have a relationship with several climates of air temperature, humidity, and rainfall, the number of branches had a relationship with climate, air climate, and rainfall. fruit bunches have a relationship with climate humidity and the amount of rainfall.